Ion channels in acinar cells in acute pancreatitis: crosstalk of calcium, iron, and copper signals - Wang, Hanli; Gao, Jianhua; Wen, Lingling; Huang, Kejun; Liu, Huixian; Zeng, Linsheng; Zeng, Zhongyi (Frontiers in Immunology, 2024)
The initial stages of acute pancreatitis (AP) are characterized by a significant event - acinar ductal metaplasia (ADM). This process is a crucial feature of both acute and chronic pancreatitis, serving as the first step in the development of pancreatic cancer. Ion channels are integral transmembrane proteins that play a pivotal role in numerous biological processes by modulating ion flux. In many diseases, the expression and activity of ion channels are often dysregulated. Metal ions, including calcium ions (Ca2+), ferrous ions (Fe2+), and Copper ions (Cu2+), assume a distinctive role in cellular metabolism. These ions possess specific biological properties relevant to cellular function. However, the interactions among these ions exacerbate the imbalance within the intracellular environment, resulting in cellular damage and influencing the progression of AP. A more in-depth investigation into the mechanisms by which these ions interact with acinar cells is essential for elucidating AP’s pathogenesis and identifying novel therapeutic strategies. Currently, treatment for AP primarily focuses on pain relief, complications prevention, and prognosis improvement. There are limited specific treatments targeting acinous cell dedifferentiation or ion imbalance. This study aims to investigate potential therapeutic strategies by examining ion crosstalk within acinar cells in the context of acute pancreatitis.